The Mediating Role of Service Quality on the Effect of Human Resource Quality and Physical Work Environment on Community Satisfaction - Santoso, Santoso; Ratnasari, Siwi Dyah (Majapahit Journal of Islamic Finance and Management, 2025)
Public service is an important foundation in government that focuses on meeting the needs of the community appropriately and efficiently. This study aims to examine the impact of human resource quality and physical work environment conditions on the level of public satisfaction, with service quality as an intermediary variable. The approach used in this study is a quantitative survey with SEM-PLS analysis tool in which the research sample is 100 respondents at the Dampit District office, Malang Regency. The findings of this study reveal that the quality of human resources has a significant positive impact on service quality. Likewise, the condition of the physical work environment also contributes positively and significantly to the quality of service. In addition, this study shows that the quality of human resources and the physical work environment directly have a positive effect on the level of community satisfaction. Service quality serves as an important factor that increases community satisfaction while mediating the effect of the quality of human resources and the physical work environment on community satisfaction. From these results, it can be concluded that improving the quality of human resources and improving the physical work environment will have a real impact on improving service quality and community satisfaction. Therefore, improving the quality of human resources and work environment conditions is very important to achieve more effective public services. It is recommended that the government increase HR training and improve work facilities to support better services. In addition, simplifying service procedures and more intensive socialization can increase public satisfaction.